Екоморфічний аналіз лучних фітоценозів Лівобережного Лісостепу України - Орлова, Л.Д. (Промышленная ботаника, 2013)
Проанализировано отношение луговых представителей флоры левобережной лесостепи Украины к экологическим факторам. Показано соотношение основных гигроморф, трофоморф, гелиоморф и климаморф на лугах отдельных типов (пойменные, суходольные и низинные) и в общем в исследованном регионе. Выявлены общие тенденции и специфические черты отдельных луговых фитоценозов. The relationships of representatives of the meadow flora in the Left-Bank forest-steppe of Ukraine to environmental factors are analyzed. The study has shown the correlation of most common hygromorphs, trophomorphs, heliomorphs and climomorphs both for certain meadow types (floodplain, dry-valley, low meadows) and for the area under investigation in general. The main trends and specific features of certain grassland plant communities were revealed.